Blowin' in the wind: Dispersal, structure, and metacommunity dynamics of aeolian diatoms in the McMurdo Sound region, Antarctica. Issue 1 (27th December 2021) - Schulte, Nicholas O.; Khan, Alia L.; Smith, Emma W.; Zoumplis, Angela; Kaul, Drishti; Allen, Andrew E.; Adams, Byron J.; McKnight, Diane M.
Abstract : Diatom metacommunities are structured by environmental, historical, and spatial factors that are often attributed to organism dispersal. In the McMurdo Sound region (MSR) of Antarctica, wind connects aquatic habitats through delivery of inorganic and organic matter. We evaluated the dispersal of diatoms in aeolian material and its relation to the regional diatom metacommunity using light microscopy and 18S rRNA high‐throughput sequencing. The concentration of diatoms ranged from 0 to 8.76 * 10 6 valves · g −1 dry aeolian material. Up to 15% of whole cells contained visible protoplasm, indicating that up to 3.43 * 10 4 potentially viable individuals could be dispersed in a year to a single 2 ‐cm 2 site. Diatom DNA and RNA was detected at each site, reinforcing the likelihood that we observed dispersal of viable diatoms. Of the 50 known morphospecies in the MSR, 72% were identified from aeolian material using microscopy. Aeolian community composition varied primarily by site. Meanwhile, each aeolian community was comprised of morphospecies found in aquatic communities from the same lake basin. These results suggest that aeolian diatom dispersal in the MSR is spatially structured, is predominantly local, and connects local aquatic habitats via a shared species pool. Nonetheless, aeolian community structure was distinct from that of aquatic communities, indicating that intrahabitat dispersal and environmental filtering also underlie diatom metacommunity dynamics. The present study confirms that a large number of diatoms are passively dispersed by wind across a landscape characterized by aeolian processes, integrating the regional flora and contributing to metacommunity structure and landscape connectivity.